Drag reduction using bionic groove surface for underwater vehicles - Zheng, Shihao; Liang, Xi; Li, Jiayong; Liu, Yanyan; Tang, Jun (Frontiers in Bioengineering and Biotechnology, 2023)
The reduction of drag is a critical issue for the shipping industry to decrease energy consumption. In this study, a novel non-smooth surface drag reduction method was developed based on the ridge structure of killer whale skin. The method employed transverse bionic groove surfaces and was numerically simulated across a wide range of flow conditions. Specifically, the study investigated the effects of periodic groove surfaces aligned perpendicular to the flow direction on the evolution of a turbulent boundary layer flow. Numerical analysis methods, employing the Shear Stress Transport k-ω model, were utilized to examine the drag reduction performance of the groove surface with varying width-to-depth ratio (λ/A), depth, and inlet velocity. The optimal shape parameters of the groove surface were determined, and the numerical simulation results showed that the bionic groove surface demonstrated good drag reduction effects in the velocity range of 2~12m/s, with a friction drag reduction ratio of 26.91% and a total drag reduction ratio of 9.63%. To compare its performance with a smooth surface, velocity gradient, streamwise mean velocity, and turbulent intensity of the bionic groove surface were analyzed. The results revealed that the bionic groove structure could reduce viscous stress and Reynolds stress, resulting in a reduction of friction drag.